Hubungan sumber air minum dan kualitas air minum secara bakteriologis terhadap kejadian diare pada anak di wilayah Permukiman Murjani Bawah di Kota Palangka Raya - Islamiyati, Sukma; Lestarisa, Trilianty; Augustina, Indria; Sri Yuliani, Ni Nyoman; Jelita, Helena (Barigas: Jurnal Riset Mahasiswa, 2023)
Diarrhea is defined as defecation with unformed stools or liquid with a frequency of more than 3 times in 24 hours.  Water can be a source of disease, this is due to disease vectors, especially diarrheal diseases, which can multiply and be transmitted through water.  The source of drinking water in the Lower Murjani Settlement area is sourced from drilled wells which are consumed by boiling first and refilling gallons of water. This study aims to determine the bacteriological relationship between the source of drinking water and the quality of drinking water on the incidence of diarrhea in children in the Lower Murjani Settlement area of ​​Palangka Raya City. This type of research is an analytic observational study with a cross-sectional design.  The sample size of 45 children was determined by purposive sampling method.  Data were analyzed using the Chi-Square statistical test. Shows that there is a relationship between the source of drinking water and the quality of drinking water on the incidence of diarrhea in children. There is a relationship between the source of drinking water and the quality of drinking water in bacteriological terms with the incidence of diarrhea in children in the Murjani Bawah residential area in the city of Palangka Raya.